TABAGISME CHEZ LES COLLEGIENS DE LA REGION DE FES-BOULEMANE (MAROC) - Louasté Bouchra; Boudine Latifa; Louasté Majda; Eloutassi Noureddine (European Scientific Journal, ESJ, 2014)
Smoking in Morocco especially among adolescents is a public health concern. To further understand the attitudes, habits and smoking behavior of Moroccan college students, a questionnaire was realized from September 2011 to May 2012, in five Moroccan colleges out of a total of 3396 students aged 10 to 18. The results shows that the prevalence of smoking is 15% and more than 50% of students surveyed were moderately to highly nicotine dependent. Girls smoke significantly less than boys, in addition, use of other psychoactive substances was reported in 67% of regular smokers. Several environmental factors influence adolescent smoking behaviors such as family, friends and the presence or absence of parents.